Dealing with brain drain: the contributions of Sri Lanka's peak business interest associations. Issue 3 (15th August 2019) - You, Kevin
Abstract : Purpose: This paper aims to investigate the way in which Sri Lankan business associations contribute to addressing such issues and the motivation behind their contributions. Design/methodology/approach: Data, in this study, came from publicly available sources (online news articles, newspaper articles, reports, etc.) and a series of unstructured elite interviews with leaders of Sri Lanka's most prominent peak business associations. Findings: Sri Lankan associations contribute to addressing problems associated with human capital flight because doing so, ultimately, benefits their members and secretariat organisations. Peak bodies make their contributions by easing the push factors that catalyse the outflow of skilled migrants from the island nation and helping to replenish skills in the country by engaging in initiatives aimed at training and developing workers, young people and entrepreneurs. Research limitations/implications: The behaviours of Sri Lanka's business interest associations and the logics that drive their actions are similar to those of their counterparts in other countries (as per academic literature in the area), where association membership is not state-mandated. Rational actions of business associations have the potential to produce socially beneficial positive externalities (as in the present case issues around the brain drain). Social implications: Findings from this research can assist government bodies, non-government organisations and other civil society organisations develop a better collaborative relationship with the private sector in developing nations to tackle problems associated with human capital flight. Originality/value: While there has been a lively debate, among philosophers and scholars of public policy, on how governments should help address issues associated with this phenomenon, very little attention has been given to the real and potential contributions of non-governmental, non-charity-based civil society groups such as unions and business chambers. This paper seeks to address this gap.